2013
DOI: 10.1128/jvi.02982-12
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Terminus of Herpes Simplex Virus 1 Glycoprotein K Is Required for Virion Entry via the Paired Immunoglobulin-Like Type-2 Receptor Alpha

Abstract: The herpes simplex virus 1 (HSV-1) glycoprotein K (gK)/UL20 protein complex is incorporated into virion envelopes and cellular membranes and functions during virus entry and cell-to-cell spread. To investigate the role of gK/UL20 in the context of a highly neurovirulent virus strain, the HSV-1(McKrae) genome was cloned into a bacterial artificial chromosome plasmid T he herpes simplex virus 1 (HSV-1) entry mechanism is both complex and unique among enveloped viruses, involving multiple glycoproteins for attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…These results are consistent with previous studies in Vero, HEp-2, CHO-PILR␣, BHK, J-nectin1, C10 murine melanoma, J-HVEM, or the neuroblastoma SK-N-SH cells (27,30,32,77,78) and the fact that low pH does not account for conformational changes in gB during fusion (79,80). Indeed, in HEp-2 and PtK 2 cells, HSV-1 infection was even more efficient when endosomal acidification, and thus presumably virion degradation, had been inhibited.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies in Vero, HEp-2, CHO-PILR␣, BHK, J-nectin1, C10 murine melanoma, J-HVEM, or the neuroblastoma SK-N-SH cells (27,30,32,77,78) and the fact that low pH does not account for conformational changes in gB during fusion (79,80). Indeed, in HEp-2 and PtK 2 cells, HSV-1 infection was even more efficient when endosomal acidification, and thus presumably virion degradation, had been inhibited.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, gC has been shown to share the same capability as gB in viral absorption (Laquerre et al, 1998). In addition, HSV-1 gK, UL20, gM, gH, gB and PILRα can assemble a complex to regulate virus-cell fusion (Chouljenko et al, 2009(Chouljenko et al, , 2010Chowdhury et al, 2013;Kim et al, 2013). The glycoproteins dispensable for membrane fusion might enhance fusion efficiency by strengthening or stabilizing the association of the fusion core machinery or by interacting with gB directly to modulate its fusion activity.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown that gK and UL20 are expressed in virion envelopes and are involved in virus entry, since deletion of gK or a small segment of gK that interacts with gB causes virions to enter more slowly than their parental wild-type virus into cells and alter their ability to utilize HSV-1-specific receptors (29,52,57). Similarly, virions produced in the absence of either gM or UL11 exhibited slower kinetics of entry into Vero cells than did their parental virus.…”
Section: Discussionmentioning
confidence: 99%